Quorum Sensing-Regulated Phenol-Soluble Modulins Limit Persister Cell Populations in Staphylococcus aureus - Bojer, Martin S.; Lindemose, Søren; Vestergaard, Martin; Ingmer, Hanne (Frontiers in Microbiology, 2018)
Incomplete killing of bacterial pathogens by antibiotics is an underlying cause of treatment failure and accompanying complications. Among those avoiding chemotherapy are persisters being individual cells in a population that for extended periods of time survive high antibiotic concentrations proposedly by being in a quiescent state refractory to antibiotic killing. While investigating the human pathogen Staphylococcus aureus and the influence of growth phase on persister formation, we noted that spent supernatants of stationary phase cultures of S. aureus or S. epidermidis, but not of distantly related bacteria, significantly reduced the persister cell frequency upon ciprofloxacin challenge when added to exponentially growing and stationary phase S. aureus cells. Curiously, the persister reducing activity of S. aureus supernatants was also effective against persisters formed by either S. carnosus or Listeria monocytogenes. The persister reducing component, which resisted heat but not proteases and was produced in the late growth phase in an agr quorum-sensing dependent manner, was identified to be the phenol-soluble modulin (PSM) toxins. S. aureus express several PSMs, each with distinct cytolytic and antimicrobial properties; however, the persister reducing activity was specifically linked to synthesis of the PSMα family. Correspondingly, a high-persister phenotype of a PSMα mutant was observed upon fluoroquinolone or aminoglycoside challenge, demonstrating that the persister reducing activity of PSMs can be endogenously synthesized or extrinsically added. Given that PSMs have been associated with lytic activity against bacterial membranes we propose that PSM toxins increase the susceptibility of persister cells to killing by intracellularly acting antibiotics and that chronic and re-occurring infections with quorum sensing, agr negative mutants may be difficult to treat with antibiotics because of persister cells formed in the absence of PSM toxins.